Effects of Alberta Family Integrated Care (FICare™) on the Health Care Resource Utilization and Cost Two Months Post-Discharge: A Cluster Randomized Controlled Trial in Neonatal Intensive Care Units. - Lopatina, Elena; Faris, Peter; Spackman, Eldon; Benzies, Karen M. (Nursing Economic$)
Alberta has the highest proportion of preterm births in Canada, which is associated with increased health service utilization and costs. The aim was to evaluate the effect of Alberta Family Integrated Care (Alberta FICare™) on health care costs compared to standard care. Data from a pragmatic cluster randomized controlled trial (cRCT) of Alberta FICare in Level II neonatal intensive care units (NICUs) were linked to administrative data on hospital admissions and emergency department (ED) visits to assess costs associated with birth admission and readmissions and ED visits within two months post-discharge -- the total cost -- per infant per group. Descriptive statistics were used to describe characteristics of the sample and unadjusted total costs. Predictive modeling compared the mean total costs between the groups, while accounting for potential confounding and stratification. A total of 718 infants from 10 NICUs were included. The mean (standard deviation) unadjusted total cost per infant was $39,649 ($19,741) and $42,195 ($20,955) in the Alberta FICare and standard care groups, respectively. Accounting for site geographic area and infant risk factors, the adjusted mean total cost per infant was lower in the Alberta FICare group ($39,434) compared to the standard care group ($41,740). The cRCT potentially lacked statistical power for this analysis, resulting in the non-statistically significant difference between the groups. Alberta FICare showed its potential to reduce the public health care system's costs. A pan-Canadian study would offer better insights in the intervention's effects on costs.